Knowledge and Attitude on Childhood Vaccination among Healthcare Workers in Hospital Universiti Sains Malaysia - Ahmad Faiq Mukhtar; Azidah Abdul Kadir; Norhayati Mohd Noor; Ahmad Hazim Mohammad (MDPI, 2022)
(1) Background: Vaccine hesitancy is recognized as an important issue globally and healthcare workers (HCWs) have a powerful influence on the public. Recent studies have reported that there are increasing numbers of vaccine hesitancies among HCWs. This study was conducted to assess the knowledge and attitudes on childhood vaccinations among HCWs in Hospital Universiti Sains Malaysia (HUSM). (2) Methods: This is a cross-sectional study conducted among one hundred and ninety-eight HCWs in HUSM, Kubang Kerian, Kelantan who were selected via convenient sampling. Data on their socio-demographic details, working experience, and main source of information regarding childhood vaccination were collected. A validated, Malay version of the knowledge and attitude on childhood vaccination (KACV) questionnaire was used during the study. (3) Results: Female (OR (95% CI):3.15, (1.39, 7.12), p < 0.05) and a higher education level (degree and above) (OR (95% CI): 2.36 (1.14, 4.89), p < 0.05) are significantly associated with good knowledge. Respondents with a history of side effects of the vaccines among their relatives were about 66% less likely to have good knowledge (OR (95% CI): 0.342 (0.16, 0.73), p < 0.05). A positive attitude towards childhood vaccination was significantly associated with a higher level of education participants, who had significantly better knowledge than participants with a lower education level (OR (95% CI): 3.81, (1.92, 7.57), p < 0.001). On the contrary, participants having direct contact with patients were less likely to have a good attitude towards childhood vaccination (OR (95% CI): 0.207 (0.043, 0.10), p < 0.05), and those with a history of severe side effects of the vaccines among their relatives were also significantly associated with a poor attitude towards childhood vaccination (OR (95% CI): 0.342 (0.16, 0.76), p < 0.05). (4) Conclusions: The survey findings showed a good level of knowledge and a good attitude of participants towards childhood vaccination. Good knowledge is important for the HCWs to have a favorable attitude to educate the general population on childhood vaccination.